Structural Reforms and the Macroeconomy: The Role of General Equilibrium Effects - Hans Gersbach (Institute for the Study of Labor (IZA), 2003)
We examine the macroeconomic consequences of industry wage bargaining and product market reforms. We suggest that general equilibrium effects may be important for the evaluation of industry-specific regulations. In particular, we suggest that the European unemployment problem can be traced back partially to insufficient recognition of general equilibrium effects. Moreover, unawareness of general equilibrium effects may be an explanation of why regulations are introduced and why structural reforms are (not) undertaken.
Keywords: J60; E24; D58; L13; 330; industry wage bargaining; structural reforms; general equilibrium effects; Deregulierung; Arbeitsmarktflexibilisierung; Tarifpolitik; Makroökonomischer Einfluß; Mehr-Sektoren-Modell; Allgemeines Gleichgewicht; Theorie